2022
DOI: 10.3390/ijerph19116443
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Curcumin in Reducing Self-Rated Pain-Levels in the Orofacial Region: A Systematic Review of Randomized-Controlled Trials

Abstract: The aim was to systematically review randomized controlled trials (RCTs) that assessed the effectiveness of curcumin in reducing self-rated pain levels in the orofacial region (OFR). The addressed focused question was “Is curcumin effective in reducing self-rated pain levels in the OFR?”. Indexed databases (PubMed (National Library of Medicine), Scopus, EMBASE, MEDLINE (OVID), and Web of Science) were searched up to and including February 2022 using different keywords. The inclusion criteria were (a) original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Pain evaluation was performed by measuring the acute post-operative pain immediately after the anesthesia effect wore off (identified as T 0 ) and eight hours after the first measurement (identified as T 1 ). 18 In the first pain evaluation, the FLACC score was measured by our #3 field researcher followed by our #4 field researcher who performed the salivary PGE 2 sample collection (please see Salivary PGE2 collection and evaluation). Once the salivary PGE 2 was collected, the curcumin patch was placed (for those in the treatment group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain evaluation was performed by measuring the acute post-operative pain immediately after the anesthesia effect wore off (identified as T 0 ) and eight hours after the first measurement (identified as T 1 ). 18 In the first pain evaluation, the FLACC score was measured by our #3 field researcher followed by our #4 field researcher who performed the salivary PGE 2 sample collection (please see Salivary PGE2 collection and evaluation). Once the salivary PGE 2 was collected, the curcumin patch was placed (for those in the treatment group).…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15][16] As an analgesic agent, including in the orofacial region, curcumin has been evaluated and delivered in several forms, capsule, gel, paste, powder, as well as in a form of a patch. 17,18 A previous study revealed that transdermal delivery of an analgesic agent, will eliminate unwanted side effects such as sedation and cognition. Additionally, curcumin delivered in a form of a transdermal patch has better optimization.…”
Section: Introductionmentioning
confidence: 99%